2013
DOI: 10.1021/jp4093404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging the Glass of Isotactic Polybutene-1 on Form II Nucleation and Cold Crystallization

Abstract: The effect of aging initially fully amorphous isotactic polybutene-1 (iPB-1) at temperatures between 243 and 283 K on form II nucleation and cold crystallization has been quantified by fast scanning chip calorimetry. Aging of amorphous iPB-1 at temperatures close to the glass transition temperature leads to formation of nuclei which accelerate subsequent cold crystallization. Analysis of the enthalpy of cold crystallization on heating differently aged samples revealed a maximum rate of nucleation at around 265… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 59 publications
4
48
0
Order By: Relevance
“…Comparison of the top and bottom sets of curves of Fig. 1.55 demonstrates that both the kinetics of nucleation and crystallization can advantageously be analyzed separately by the experimental approach applied here, and the companion studies on PCL, iPB-1, or iPP [38,100,125,127]. For example, formation of crystal nuclei begins after about 10 s on annealing amorphous PA 6 at 333 K, while crystal growth connected with exchange of latent heat is only observed after 1000 s (see upper and lower dashed-dotted curves).…”
Section: Summary Of Experimental Results and Conclusionmentioning
confidence: 96%
See 1 more Smart Citation
“…Comparison of the top and bottom sets of curves of Fig. 1.55 demonstrates that both the kinetics of nucleation and crystallization can advantageously be analyzed separately by the experimental approach applied here, and the companion studies on PCL, iPB-1, or iPP [38,100,125,127]. For example, formation of crystal nuclei begins after about 10 s on annealing amorphous PA 6 at 333 K, while crystal growth connected with exchange of latent heat is only observed after 1000 s (see upper and lower dashed-dotted curves).…”
Section: Summary Of Experimental Results and Conclusionmentioning
confidence: 96%
“…We studied a commercial iPB-1 grade PB0110M from Basell Polyolefins synthesized using a Ziegler-Natta catalyst [100]. The mass-average molar mass and polydispersity are Brought to you by | Stockholms Universitet Authenticated Download Date | 7/7/15 5:06 AM 711 kDa and 6.5, respectively, and the melt-flow rate (190 ∘ C, 2.16 kg) is 0.4 g (10 min) −1 [101].…”
Section: Isotactic Polybutene-1 (Ipb-1)mentioning
confidence: 99%
“…In this context, it has been recently reported that the aging at temperatures close to the glass transition leads to formation of crystal nuclei responsible for the acceleration of the subsequent crystallization [15][16][17]35,36].…”
Section: Structural Relaxation In the Glass Transition Regionmentioning
confidence: 99%
“…Analysis of the crystallization behavior of vitrified samples of PCL [14,32], PA 6 [33] and isotactic polybutene-1 (iPB-1) [34] revealed furthermore that during annealing of the glass there is first observed enthalpy relaxation, and only after its completion there is detected crystal nucleation followed by crystal growth. The decrease of the enthalpy of the glass to the value of the liquid state corresponds to a densification of the glass, involving cooperative rearrangement of molecule segments on a lengthscale of few nanometers, eventually leading to formation of small clusters of parallel aligned chain segments, to be considered as homogeneous nuclei if being of supercritical size.…”
Section: Introductionmentioning
confidence: 99%